An Investigation Of The Factors That Impact The Intention To Adopt And Use Mict In The Libyan Construction Industry - Sheglabo, Jamal; McGill , Tanya; Dixon, Michael (Penerbit Universiti Sains Malaysia, 2017)
Information technology has been identified as a vital means for supporting construction project processes, but the level of adoption in the construction industry has been low relative to other sectors. Mobile Information and communications technology (mICT) allows people to access information from wherever they are, and as work in the construction industry is mainly fieldwork with highly mobile workers, mICT holds promise for the sector, particularly in developing countries. The aim of the study reported in this paper was to investigate factors that could impact stakeholders' adoption of mICT in the Libyan construction industry. A model of mICT adoption was developed and tested using data collected from a survey of 202 construction industry stakeholders from 15 companies in Libya. The analysis was undertaken using structural equation modelling. It was found that perceived usefulness and ease of use are important in determining the intention to adopt mICT and that they are influenced by self-efficacy and facilitating conditions. The cost of technology was not found to be a barrier to adoption. Recommendations are made to the construction industry in Libya and relevant government authorities to help improve awareness of the potential of mICT and to help improve potential users' self-efficacy.